(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article presents a detailed analysis of the clinical and morphological features of psoriasis in children and adolescents. The authors describe in detail the pathognomonic elements of skin eruptions, their localization, and the dynamics of their development depending on the form of the disease. Special attention is paid to the algorithms of comprehensive diagnosis and the analysis of the effectiveness of current therapeutic methods. A modern approach to the treatment of psoriasis is formulated, aimed at achieving stable remission and preventing the appearance of new papules.